Deep-water decapod crustaceans studied with a remotely operated vehicle (ROV) in the Marquesas Islands, French Polynesia (Crustacea: Decapoda) - Poupin, Joseph; Corbari, Laure; Pérez, Thierry; Chevaldonné, Pierre (Zootaxa, 2012)
Decapod crustaceans were studied in the Marquesas Islands, French Polynesia, between 50–550 m by using a remotelyoperated vehicle (ROV) equipped with high resolution cameras and an articulated arm. Careful examination of videos andphotographs combined with previous inventories made in the area with conventional gears allowed the identification of30 species, including 20 species-level determinations. Species identified belong to shrimps (Penaeoidea, Stenopodidea,and Caridea), lobsters (Astacidea and Achelata), anomurans (Galatheoidea and Paguroidea), and brachyuran crabs(Dromioidea, Homolodromioidea, Raninoidea, Leucosioidea, Majoidea, Parthenopoidea, Portunoidea, and Trapezioidea).Most of these species were observed and photographed in situ for the first time. A discussion is given on the geographic distribution, density, ecology, and behavior.